Управління економічними ризиками у діяльності морських туристичних компаній - Балджи, Марина Дмитрівна; Балджи, М. Д. (My University, 2022)
Діяльності морських туристичних компаній притаманна наявність значної кількості різних економічних ризиків. У статті зроблено спробу визначити схильність морських туристичних компаній до ризику на основі розкриття інформації в їх фінансовій звітності. Оригінальністю дослідження виступає виявлення економічних ризиків для морських туристичних компаній, що базується на імовірнісному підході до визнання подій. У статті розглянуто теоретичні основи вивчення ризиків туристичних компаній, виділено методи подальшого дослідження, проаналізовано стан наукових пропозицій у виявленні економічних ризиків та перспективи використання моделювання, обґрунтовано аспекти управління економічними ризиками на основі використання фінансової звітності при побудові моделей, запропоновано шляхи використання напрацювань для розробки стратегій управління економічними ризиками. Визначено, що морські туристичні компанії розкривають фактори ризику за допомогою не- структурованих даних. Для виявлення схильності до ризику, розкритої у фінансовій звітності морських туристичних компаній, використана тематична модель «Прихований розподіл Діріхле пропозиції» (Sent-LDA), яка є розширенням вихідної моделі прихованого розподілу Діріхле (LDA). В результаті дослідження доведено універсальність та ре- презентативність економічних ризиків; визначено, що морським туристичним компаніям притаманний ризик розширення бізнесу, ризик партнерства, ризик зміни попиту, сезонний ризик, ризик харчування та карантин. Результати дослідження можуть бути використані зацікавленими сторонами для розробки доцільних та своєчасних стратегій управління економічними ризиками.

The activities of maritime tourism companies are characterized by a significant number of various economic risks. The article attempts to determine the exposure of maritime tourism companies to risk based on the disclosures in their financial statements. The originality of the study is the identification of economic risks for maritime tourism companies, which is based on a probability approach in recognizing events. The article discusses the theoretical foundations for studying the risks of travel companies, highlights methods for further research, analyzes the state of scientific proposals in identifying economic risks and the prospects for using modeling, substantiates aspects of managing economic risks based on the use of financial reporting when building models, and suggests ways to use to develop management strategies dealing with economic risks. The interpretation of the risk of a maritime tourism company is proposed as the unpredic- tability of a negative impact on the results of decision-making and on the general conditions that they may encounter in the daily business process, due to limited unknown events. It has been determined that maritime tourism companies disclose risk factors using unstructured data, and this makes it difficult to determine the types of risk using traditional econometric methods. The Latent Dirichlet Allocation (Sent-LDA) thematic model, which is an extension of the original Latent Dirichlet Allocation (LDA) model, was used to identify exposures disclosed in the financial statements of maritime tourism companies. To identify the parameters of the LDA model for financial documents, Gibbs sampling was used, that is, an algorithm to create a sample of the joint distribution of a set of random variables. The study proved the universality and representativeness of economic risks; Maritime tourism companies have been proven to have business expansion risk, partnership risk, demand risk, seasonal risk, food risk and quarantine risk. At the same time, endogenous and exogenous components are considered: according to the first, each enterprise has its own unique business characteristics, and the identification of economic risks is realistic on the basis of financial statements; according to the second, studies of economic risks are aimed at increasing the competitiveness of enterprises in the service sector market. The results of the study can be used by stakeholders to develop appropriate and timely economic risk management strategies.
Балджи М. Д. Управління економічними ризиками у діяльності морських туристичних компаній / М. Д. Балджи // Розвиток методів управління та господарювання на транспорті : Зб. наук. праць. – 2022. – №. 1(78). – С. 106-117. DOI 10.31375/2226-1915-2022-1-106-117
Keywords: економічні ризики; ризик-менеджмент; фінансова звітність; модель LDA і Sent-LDA; морські туристичні компанії; economic risks; risk management; financial reporting; model LDA &Sent-LDA; maritime travel companies; Research Subject Categories::SOCIAL SCIENCES::Business and economics